MENINGKATKAN ADVERSITY QUOTIENT SISWA MENGGUNAKAN AUTOGRAPH - Ely Syafitri; Sahat Saragih; E. Elvis Napitupulu; KMS. Muhammad Amin Fauzi; anim anim; Elfira Rahmadani; Syahriani Sirait; Ismail Hanif Batubara (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2022)
Abstract. This study aims to determine the difference in  adversity quotient between students who learn to use the Autograph learning media and students who receive conventional learning. The formulation of the problem in this study is "Is there a difference between the adversity quotient of students who learn to use Autograph learning media and students who receive conventional learning?". This research is a quasi-experimental research, where the teacher plays a direct role in the learning process and the researcher acts as an observer. The subjects in this study were students of class VIII MTs Al-Arifin Rahuning totaling 100 people and as a sample of class VIII-1 totaling 28 people. While the object of this research is the adversity quotient of students towards learning mathematics. Collecting data in this study using observation sheets and adversity quotient. To find out the results of this study, it was carried out using the t test and to determine whether or not there were differences in the adversity quotient of students towards learning mathematics. Based on the results of data analysis carried out, it was concluded that there was a difference in the adversity quotient between students who learned to use the Autograph learning media and students who received conventional learning with a tcount= 8.29 greater than ttable at the 5% significance level and significant 1% of 2.14 and 2.96.Keyword: Autograph, Adversity Quotient, Mathematic educationAbstrak. Penelitian ini bertujuan untuk mengetahui perbedaan adversity quotient antara siswa yang belajar menggunakan media pembelajaran Autograph dan siswa yang mendapatkan pembelajaran konvensional. Rumusan masalah dalam penelitian ini adalah “Apakah ada perbedaan antara adversity quotient siswa yang belajar menggunakan media pembelajaran Autograph dengan siswa yang mendapatkan pembelajaran konvensional?”. Penelitian ini merupakan penelitian eksperimen semu, dimana guru berperan langsung dalam proses pembelajaran dan peneliti bertindak sebagai pengamat. Subjek dalam penelitian ini adalah siswa kelas VIII MTs Al-Arifin Rahuning yang berjumlah 100 orang dan sebagai sampel kelas VIII-1 yang berjumlah 28 orang. Sedangkan objek penelitian ini adalah adversity quotient siswa terhadap pembelajaran matematika. Pengumpulan data dalam penelitian ini menggunakan lembar observasi dan adversity quotient. Untuk mengetahui hasil penelitian ini dilakukan dengan menggunakan uji t dan untuk mengetahui ada tidaknya perbedaan adversity quotient siswa terhadap pembelajaran matematika. Berdasarkan hasil analisis data yang dilakukan, disimpulkan bahwa terdapat perbedaan adversity quotient antara siswa yang dibelajarkan menggunakan media pembelajaran Autograph dan siswa yang mendapatkan pembelajaran konvensional denganhitung= 8,29 lebih besar dari ttabel sebesar 5 % tingkat signifikansi dan signifikan 1% sebesar 2,14 dan 2,96.